Pengaruh Model Problem Based Learning Berbasis Kearifan Lokal Terhadap Keterampilan Berfikir Kritis Siswa Kelas IV Sekolah Dasar - Asterli, Neni Tria; Imansyah, Farizal; Marleni, Marleni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The problem behind this research is that the teacher is still not optimal in using the learning model, the lack of interaction between the teacher and students during learning takes place and student learning outcomes are still relatively low. The purpose of this study was to examine the improvement of PPkn learning outcomes for students in class II who received learning through the Contextual Teaching and Learning Learning Model better than students who received the ordinary learning model without going through the Contextual Teaching and Learning Learning Model in Class II Elementary School. This research is a quantitative research with the type of experimental method The subjects in this study were students of class II.A and II.B, totaling 46 students. The instrument used in this study was a short essay/short-test question totaling 11 questions. Analysis of the data in the study used the SPSS version 22 application. When viewed from the results of the t-test calculation with a significant value of 0.000 less than 0.025, it is stated that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant increase in PPkn learning outcomes through the Contextual Teaching and Learning learning model in grade II Elementary School.